Examining the working conditions of food delivery riders in Iloilo City Karla Suzzaine R. Eballa. - Eballa, Karla Suzzaine R.
This phenomenological study examines the working conditions of food delivery riders in Iloilo City. It described the socioeconomic and employment profile of the food delivery riders, working conditions, and other issues and concerns related to their work. Data were gathered through questionnaires, semi-structured interviews, key informant interviews, and secondary data review. Research findings were analyzed using thematic analysis and recommendations have been generated that aim to improve the working conditions of food delivery riders. Majority of the food delivery riders involved in this study are male, single, and with college education. Food delivery is their main source of income, and they work almost every day. Food delivery riders .